Ergonomic Risk Assessment of Factory Workers in Selected Wooden Sawmill Industries in Port Harcourt, Rivers State - Ukpong-Udo, Kufre; Ugbebor, J. N.; Wejie-Okachi, C. (European Journal of Applied Sciences, 2023)
This study was conducted with the aim of assessing the ergonomic risks which wooden sawmill workers are exposed to in Port Harcourt, Rivers State. A total of 9 medium to heavy wooden sawmills were considered for the study, and 65 sawmill workers that fulfilled a confidence level of 95% of the study population were selected as respondents through purposive sampling. Data was collected through a structured questionnaire and oral interviews, and the results were analyzed using Statistical Package for Social Sciences (SPSS Version 20). Descriptive and inferential statistics were used for data analysis, and results were presented in the form of frequency tables, and graphs. The study revealed that over 55% of wooden sawmill workers have poor knowledge of ergonomics. The study also revealed that 65% of sawmill workers are exposed to physical, mental and organizational ergonomic risk factors, including repetitive stationary tasks, use of heavy and vibrating machines, and exposure to musculoskeletal disorders MSDs. The study showed that wooden sawmill workers are exposed to medium (Rapid Entire Body Assessment risk index = 4) to very high (Rapid Entire Body Assessment risk index = 11), risks of musculoskeletal disorders depending on which activities they engage in within the wooden sawmill industry. The study highlights the need for education and awareness of ergonomics among wooden sawmill workers, and for implementing proper safety procedures and work design to reduce the risk of ergonomic incidents and promote workers health and wellbeing.